1986
DOI: 10.1159/000167328
|View full text |Cite
|
Sign up to set email alerts
|

Renal Hemodynamic Effects of Tertatolol Compared with Those of Propranolol in the Conscious Dog

Abstract: Experiments were performed in which the effects of two β-blockers, tertatolol [dl-(hydroxy-2’-t-butyl-amino-3’-propyloxy)-8-thiochroman hydrochloride] and propranolol, on mean arterial pressure (MAP), heart rate (HR), and renal function were studied in the conscious sodium-replete dog. In all experiments renal function was evaluated from the effective renal plasma flow (ERPF) and glomerular filtration rate (GFR) assessed respectively by measurement of p-aminohippurate and creatinine clearances. These parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

1986
1986
1990
1990

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…Indeed, a renal function impair ment is generally observed when this treatment is intro duced and continues with long-term administration [8,9]. In contrast, this 1-year study confirms the beneficial effect of tertatolol on renal function previously observed in experimental [17,18] and short-term studies [19][20][21], Particularly, in keeping with what was reported by Ardaillou [20], the decrease in plasma creatinine level is greater the greater the initial level is. and reaches almost 20% in the upper-range subgroup.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Indeed, a renal function impair ment is generally observed when this treatment is intro duced and continues with long-term administration [8,9]. In contrast, this 1-year study confirms the beneficial effect of tertatolol on renal function previously observed in experimental [17,18] and short-term studies [19][20][21], Particularly, in keeping with what was reported by Ardaillou [20], the decrease in plasma creatinine level is greater the greater the initial level is. and reaches almost 20% in the upper-range subgroup.…”
Section: Discussionsupporting
confidence: 87%
“…One of the reasons supposed to account for this phenomenon is the lack of any important salt and water retention during ß-blocker treatment, as shown by the stability of the patient's body weight during this study. The effects of tertatolol on renal function [17][18][19][20][21][22] further support this explanation.…”
Section: Discussionmentioning
confidence: 90%
“…It also has some pecu liar properties regarding renal hemodynamics. Laubie et al [29] and Walker et al [30] have shown that renal plasma flow measured by paraaminohippurate clearance and GFR measured by inulin clearance are unaffected by intravenous administration of tertatolol [29,30]. In spontaneously hypertensive rats, Struyker-Boudier et al [31] have shown that tertatolol induces a reduction of renal vascular resistance.…”
Section: Discussionmentioning
confidence: 99%
“…a redistribution towards the hepatosplanchnic circulation has also been shown [19], Finally, the best example is given by the (3-blocking drug tertatolol: while cardiac output is reduced and total peripheral resistance elevated, a striking vasodilation in the kidney is ob served at the same time. Following acute administration, the preserved renal plasma flow observed with tertatolol appears to be the consequence of a lack of vasoconstric tion within the kidney; this takes place in the context of a systemic vasoconstriction [20][21][22]. Following chronic administration, the preserved or increased renal plasma flow appears to be the consequence of renal vasodilation, this takes place in the context of the long-term adapta tion of vascular resistance [20][21][22][23].…”
Section: Redistribution O F Vascular Resistancementioning
confidence: 99%
“…Following acute administration, the preserved renal plasma flow observed with tertatolol appears to be the consequence of a lack of vasoconstric tion within the kidney; this takes place in the context of a systemic vasoconstriction [20][21][22]. Following chronic administration, the preserved or increased renal plasma flow appears to be the consequence of renal vasodilation, this takes place in the context of the long-term adapta tion of vascular resistance [20][21][22][23]. Furthermore, the vasodilation is more effective in the presence of an ini tial background of renal vasoconstriction, as can be observed in sustained essential hypertension, thus result ing in an absolute increase in renal plasma flow.…”
Section: Redistribution O F Vascular Resistancementioning
confidence: 99%